Topical use of tranexamic acid in open heart surgery - Chaudhary, Farid Ahmad; Pervaz, Zahid; Ilyas, Sana; Niaz, Muhammad Nabeel (Journal of the Pakistan Medical Association, 2018)
To determine the efficacy of topical pouring of tranexamic acid in reducing post-operative mediastinal bleeding, requirement for blood products and the rate of re-exploration for re-securing haemostasis or relief of pericardial tamponade after open heart surgery. The prospective, randomised, placebo-controlled, double-blind comparative study was conducted from March 2013 to September 2015 at Rehmatul-lil-Alameen Institute of Cardiology, Punjab Employees Social Security Institution, Lahore, and comprised patients scheduled for primary isolated elective or urgent open heart surgery. The subjects were divided into two equal groups. The hetranexamic acid group received cardiac bath with 2gm of tranexamic acid diluted in 50mlof normal saline, while the placebo group received cardiac bath without tranexamic acid. Before the closure of sternum, the solution was poured into pericardial cavity as cardiac bath while the chest tubes were temporarily clamped. Data was entered into a pre-designed proforma. Of the 100 subjects, there were 50(50%) in each of the two groups. There was no difference in surgical characteristics and perioperative complications in the groups (p>0.05). After 48 post-operative hours, total blood loss was significantly less in the tranexamic acid group compared to the placebo group (p<0.05). Significantly less number of blood pints were transfused in the acid group than the placebo group (p<0.05). No patient in the acid group was re-explored for excessive bleeding compared to 4(8%) in the placebo group. There was significant reduction in post-operative blood drainage, need of blood products and rate of re-exploration after topical use of tranexamic acid in open heart surgery.